Characterizing the Risk of Long-Term Opioid Utilization in Patients Undergoing Lumbar Spine Surgery. Issue 1 (1st January 2020) - Wright, Anna K.; Sikora, Matt; Leveque, Jean-Christophe
Abstract : Study Design: Single-institution retrospective cohort study. Objective: To determine whether prescribing practices at discharge are associated with opioid dependence (OD) in patients undergoing discectomy or laminectomy procedures for degenerative indications. Summary of Background Data: Long-term opioid use in spine surgery is associated with higher healthcare utilization and worse postoperative outcomes. The impact of prescribing practices at discharge within this surgical population is poorly understood. Methods: A query of an administrative database was conducted to identify all patients undergoing discectomy or laminectomy procedures at our high-volume tertiary referral center between 2007 and 2016. For patients included in the analysis, opioid prescription data on admission and discharge were manually abstracted from the electronic health record, including opioid type, frequency, route, and dose, and then converted to daily morphine equivalent dose (MED) values. We defined OD as a consecutive narcotic prescription lasting for at least 90 days within the first 12 months after the index surgical procedure. Results: Of the 819 total patients, 499 (60.9%) patients had an active opioid prescription before surgery. Postoperatively, 813 (99.3%) received at least one narcotic prescription within 30 days of index surgery, and 162 (19.8%) continued with sustained opioid use in the 12 months after surgery. In adjusted analysis, patients with OD had a higher incidence of preoperative depression ( P  = 0.012) and preoperative opioid use ( P  < 0.001), as well as a higher frequency of preoperative benzodiazepine prescriptions ( P  = 0.009), and discharge MED value exceeding 120 mg/day ( P  = 0.013). Postoperative OD was observed in 7.5% of previously opioid-naïve patients. Conclusion: This is the first study to test for an association between MED values prescribed at discharge and sustained opioid use after lumbar spine surgery. In addition to previously reported risk factors, discharge prescription dose exceeding 120 mg/day is independently associated with OD after spine surgery. Level of Evidence: 3 Abstract : The aim of this study was to determine whether prescribing practices at discharge are associated with opioid dependence in patients undergoing discectomy or laminectomy procedures for degenerative indications. This is the first study to demonstrate an association between discharge presription dose exceeding 120 mg/day and sustained opioid use after lumbar spine surgery.